The Words that Abu al-Tayyib al-Lughawi does not Accept as Addad (Contronym) in the Context of Kitab al-Addad - Meydanoglu, Ayse (Cumhuriyet Univ, Fac Theology, 2018)
In this study, the words that Abu al-Tayyib al-Lughawi did not consider as addad while his predecessors accepted the same words as addad (contronym), are examined. These words are examined with the purpose of determining his approach towards contronmy words (addad). There is disagreement about the definition and the number of addads, which can shortly be defined as the word which has two opposite meanings. In this study, brief information about the definition and limitation of addad and the reasons that produce addad are given, and then the words that Abu al-Tayyib does not accept as addad are analysed under the four titles - based on the classification made by himself. The author does not accept the words which have the same ism al-fa'il (active participle) and ism al-maful (passive participle) format because of the verb's being ecwef or the middle letter's being combined with the final letter of the verb as addad. Besides, he does not accept the words that have two opposite meanings due to their figurative meaning as addad. He also states that he does not take the words included in addad category just because their meanings are reversed by Arabs as addad. With this attitude, the author has rendered the concept more comprehensible by showing what is not addad. In this study, Abu al-Tayyib's work named Kitab al-addad is taken as the primary text, and the pieces of poetry and prose shown as examples by the author are stated with their primary sources. Summary: There are many scholars who worked on addad, which is a terminological expression for the words that have two opposite meanings. Abu al-Tayyib al-Lughawi is one of the scholars to write a work about this subject. The author had the opportunity to examine most of the studies about addad and making a comparison between these studies, he wrote Kitab al-addad fikalam al-'Arab. The work was composed by arranging the words, which had been accepted as addad by the former scholars, in an alphabetical order according to their initial letters alone. The author completed his work by using expressions showing his objection or confirmation about the words' being addad or not while mentioning the words. Abu al-Tayyib added an addendum to the end of the work and in this section, he noted some words which the former scholars had accepted as addad but he did not. Although he explained the reason of adding this addendum as not to be thought of unaware of these words, he aimed to correct a mistake made by the previous linguists by identifying it thanks to the mentioned addendum. The words (used both with the meaning of black and white), (to arise and to set), (night and day), (big and small) and (dark and light) can be given as examples for the concept of addad, which is terminologically used for the words having two opposite meanings. The words such as (to sell and to buy), (sighted and blind), (to repair and to bring down), (green and black), (well-fed calf/camel and undernourished calf/camel, which have two opposite meanings at the same time, are among the words that Abu al-Tayyib presents as addad in his work. Although there are various definitions of addad, the clearest and most comprehensive one belongs to Abu al-Tayyib. He makes the following definition which distinguishes addad from common wording: addad is the plural form of didd (antonym). Antonym means the opposite of something, such as black and white, generosity and meanness, courage and cowardice. Everything that is opposite of something is not necessarily the antonym of it. For example, although strength and ignorance are two opposite words, they cannot be taken as antonyms. Because, the antonym of strength is weakness and the antonym of ignorance is knowledge. This difference arises from the fact that the term opposite is more comprehensive than the term antonym. Although all addad words are opposites, not all the opposite words are antonyms (addad). The biggest controversy about addad is about the number of the words that are accepted as addad. While some scholars represent the numbers of addad words in Arabic language as four hundred, they are not more than twenty for some other scholars. In spite of the controversy about the numbers of addad words in the language, the existence of addad in Arabic language is an accepted situation. There are some reasons leading to addad in Arabic language, one of which is dialect difference. The word which is used for the meaning of dark by Temim clan means light in Kays tribe. Some changes in language are also stated among the reasons causing addad. It is stated that the original meaning of the word was interrupted, but then it was used with the meaning of both night and day for the reason that night is interrupted by day and day is interrupted by night. Another reason is purported as being psychological and social factors. Using the term generous to make fun of a mean person is an example for this situation. One of the reasons causing addad is the morphological structures of the words. As it is the case with the word frightened/frightening, the use of ism al-fa'il and ism al-maful modes in the same form has caused to using the same word with two opposite meanings. There are also some scholars who accept the words that gain two opposite meaning to each other because of rhetorical factors like metaphor. Using the word both with the meaning of fire and metaphorically the pit where fire is lighted is an example for this sort. The scholars' acceptance or rejection of the reasons leading to addad has resulted in their expanding or narrowing the numbers of addad words in the language. In this context, the numbers of addad words are more for a scholar who accepts most of the reasons mentioned. Abu al-Tayyib is among the scholars to cast a wide scope for addad words. Since the author accepts the addad words arising from dialect and metre difference, the words that he takes as addad are quite many. In Kitab al-addad, he states that there are total of 320 addad words and at the same time he collects the words that he does not accept as addad but which were accepted so by the former scholars under four headings. In the first group, there are the words thought as addad because of being an ecwef verb. For the author, the reason these words are supposed to be addad is that ism al-fa'il (active participle) and ism al-maful (passive participle) modes of these words turn into the same structure as a result of 'ilal rules. The fact that means both the one who wears and the thing that is worn; is used as ism al-fa'il with the meaning of the one who buys stuff and as ism al-maful with the meaning of the stuff sold is an example for this situation. In the second group, there are the words which are taken as addad because of merging (idgham) middle letter of the word to its final letter. It is seen that ism al-fail and ism al-maful forms of these words are the same due to various reasons. The fact that is used both for disguised and the place to disguise; is used for the one who gathers grass and the grass gathered is of this sort. In the third group, there are words which are assumed to be addad as they are named after their reasons. There is mostly metaphorical meaning in the words that are placed in this group. One of the words that Abu al-Tayyib presents as an example to this group is Aqiqa means the hair on the head of the baby when it is born. An animal is sacrificed when this hair is shaved. In time, the animal sacrificed has begun to be called as 'aqiqa, as well; and so, 'aqiqa is used both for the hair and the sacrifice. Abu al-Tayyib argues that such words are absolutely not addad. In the fourth group, there are expressions that result from fa'il's replacing maful and maful's replacing fa. il or the words that appear in similar ways. For instance, using the expression the lizard climbed up the tree not with the common usage but by changing the places of fa'il and maful is an example for this group. Abu al-Tayyib objects to the acceptance of the words used in this way as addad, and argues that aforesaid usages do not comply with the definition of addad.
Kitâbü'l-Ez?dâd özelinde Ebü't-Tayyib el-Lugavî'nin ez?dâd'dan kabul etmediği kelimeler
Keywords: Arabic Language and Rhetoric; Language; Abu al-Tayyib al-Lughawi; Addad (Contronym); Kitab al-addad